Escolha de gruas para construção de edificações verticais: Estudo de casos na região metropolitana do Recife, Brasil - Santos, F. J. B. (2019)
Cranes play an important role at construction sites, transporting heavy loads and large volumes efficiently. The use of the crane, besides reducing manual labor and requiring a more skilled workforce, enables the introduction of new building techniques only possible with the use of this equipment. International studies have shown that the planning process for this equipment is complex, involving multiple stakeholders, and is influenced by two types of factors: hard factors, such as the technical characteristics of the equipment (physical dimensions of the site and required load capacity) and soft factors, which include qualitative specifications of an informal nature (safety characteristics of the company, purchasing/rental policies, and environmental constraints). In this context, understanding the planning process (selection and location) of tower cranes used at vertical building sites is of paramount importance in order to improve management systems for this equipment. Therefore, the objective of this work is to conduct a study of the use of tower cranes at vertical construction sites in the Recife Metropolitan Area (RMR) in order to determine the current state of practice for selecting and using this equipment. The study was conducted at ten vertical building sites (eight in Recife and two in Jaboatão - PE) belonging to eight different construction companies. The survey form was developed based on previous studies of cranes in the USA and Israel, was improved through application at 18 Portuguese building projects, and adapted to the reality of Brazilian buildings through a pilot project at two construction sites in Recife. The forms were filled out during personal visits and semi-structured interviews, lasting an average of four hours. Two worksite supervisors, one mechanical engineer, and ten civil engineers residing at the analyzed sites were interviewed. In order to increase the reliability of the research, complementary data from multiple sources was used to augment the interviews, such as construction documentation, direct observation of crane operation, and photographic records. Data analysis was performed using Excel spreadsheets and this indicated the existence of cultural factors in the selection and location of equipment, such as a preference for the use of internally climbing cranes located in the structural core of the building or running through openings in the floor slabs. According to the interviewees, the selection, planning, and location of cranes happen solely during the preparation and planning phases (preconstruction) of the construction project, with the construction supervisor and the resident engineer being the key stakeholders involved in this process. The study presents limitations regarding the generalization of results depending on the sample type adopted. Therefore, it is recommended to increase the number of construction sites analyzed and develop a multi-criteria decision support model that can assist the process of selection and location of cranes in the RMR.